Psychosocial Outcomes of Sharing a Diagnosis of Cancer with a Pediatric Patient - Raz, Haya; Tabak, Nili; Kreitler, Shulamith (Frontiers in Pediatrics, 2016)
Purpose: This innovative pilot study was designed to provide research-based evidence on the variables to consider informing a child of his/her cancer diagnosis, so as to minimize the negative psychosocial effects of the cancer experience on survivors. The hypotheses of the study were that 'good information' about cancer, will allow the child a better understanding way to cope with treatment and improve socio-psychological outcomes at adulthood. Methods: Ninety-one adult childhood cancer survivors got the questionnaires while waiting to their routine checkup at a grate childhood cancer medical center in center Israel. Results: To our surprise and not according to the hypothesis, there was a difference between children diagnosed up to 12 years of age and those diagnosed during adolescence. (Participants were divided into two groups according to their age at diagnosis: from birth to 12-years-old and from age 12 to 18). In the group diagnosed at a younger age, those who had received "good information" were found to have better quality of life, lower mental pain and higher mental pain tolerance than did those in the same group (diagnosed at a younger age) who received "not good information". By contrast, in the group diagnosed during adolescence, those who had received "not good information" scored higher on these measures than did their counterparts who had received "good information". Conclusions: Given that information conveyed to children diagnosed with cancer can have a significant impact on survivors' quality of life, further research is needed to determine the precise information to be divulged to children at the time of diagnosis. In the meantime, extreme caution, sensitivity, and careful judgement are required. Clinical Relevance: Findings the current study and of future studies can be used to formulate clear guidelines for assessing a child's readiness and the information to be divulged, so as to improve the quality of life of childhood cancer survivors. Keywords: childhood cancer, information, childhood cancer survivors, quality of life, mental pain, meaning.